2015
DOI: 10.1586/14779072.2015.1036741
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for managing aortoiliac occlusions: access, treatment and outcomes

Abstract: Treatment of severe aortoiliac disease has dramatically evolved from a dependence on open aortobifemoral grafting to hybrid and endovascular only approaches. Open surgery has been the gold standard treatment of severe aortoiliac disease with excellent patency rates, but with increased length of stay and major complications. In contrast, endovascular interventions can successfully treat almost any lesion with decreased risk, compared to open surgery. Although primary patency rates remain inferior, secondary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 62 publications
2
48
0
3
Order By: Relevance
“…12,29,30 Some recommend endovascular therapy as first-line for all patients regardless of anatomy. 31 However, long-term results in patients with extensive disease remain largely unknown. With this in mind, the value of ABF is diminished in patients with short life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…12,29,30 Some recommend endovascular therapy as first-line for all patients regardless of anatomy. 31 However, long-term results in patients with extensive disease remain largely unknown. With this in mind, the value of ABF is diminished in patients with short life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of aortic graft infection after open and endovascular aortic surgery is low, at 0.5-6%, but carries a mortality that may be as high as 88% [1,[12][13][14][15][16] Factors other than surgeon experience may influence the rate of morbidity and mortality after aortoiliac revascularization. In their retrospective review, Vogel and colleagues found that patients with perioperative bloodstream septicemia and surgical site infections were at significantly increased risk for developing AGI than those without such infections (0.93% vs. 0.18%, p=0.014; 1.61% vs. 0.19%, p=0.01), with the highest risk during the first postoperative year [13].…”
Section: Discussion Incidencementioning
confidence: 99%
“…Thus, the decision to choose open anatomic bypass is strongly challenged by percutaneous treatment, that should be considered a first-line treatment option for all patients with aortoiliac disease, especially for patients with an inoperable condition [15][16][17]. Quoting Clair DG and Beach JM, "the decision as to whether to choose anendovascular or open intervention requires a balance between the extent of thepatient's disease, the ability for thepatient to withstand a significant open operation without serious complication, and the surgeon's comfort and expertise in both open and endovascular aortoiliac procedures" [18].…”
Section: Case Journal Of Case Reports and Studiesmentioning
confidence: 99%